-SO3H-functionalization of sub-bituminous coal as a highly active acidic catalyst during the transesterification of spent sunflower oil; characterization, application, and mechanism. (November 2021) - Ibrahim, Sherouk M.; El-Sherbeeny, Ahmed M.; Shim, Jae-Jin; AlHammadi, Ali A.; Abukhadra, Mostafa R.
Abstract: Raw coal without carbonization was treated with sulfuric acid at different concentrations (70% to 95%) as a controlled sulfonation process to produce a simple and effective acidic catalyst. The synthetic catalyst (S.Coal) at the best H 2 SO4 concentration (95%) showed the best acid density (8.4 mmol/g), the best surface area (26.4 m 2 /g), and the best catalytic activity during the transesterification of the waste sunflower oil. The best yield (98.8%) at low-temperature conditions (40 °C) was achieved after 60 min using 3 g of the catalyst and at a methanol/oil ratio of 20:1. At high-temperature conditions (120 °C), the yield was enhanced to 99.5% after 30 min only considering the catalyst quantity and the methanol content as the same values. The S.Coal as a catalyst is of remarkable reusability for five transesterification runs either at low-temperature conditions (40 °C) or at high-temperature conditions (120 °C). Additionally, the catalyst is of higher catalytic performances than several basic and acidic catalysts demonstrate the efficiency of the sulfonation process on the raw coal without carbonization. The kinetic properties of the occurred transesterification reactions over S.coal followed the Pseudo-First order behavior and of low activation energy. Graphical abstract: Highlights: -SO3 H/coal was used as an effective and low cost heterogeneous acidic catalyst. It was used in transesterification of spent oil at room and supercritical conditions. It achieved actual yields of 98.8% and 99.5% at 40 °C and 120 °C, respectively. The produced biodiesel samples match the international specifications of biofuels. It is of high recyclability, Pseudo-first-order kinetics, and low activation energy.